Clinical presentation of vernal keratoconjunctivitis in an immunocompromised patient: a case report - Minhas, Shailender; Tuli, Rajeev; Sharma, Gaurav (International Journal of Scientific Reports, 2019)
Vernal keratoconjunctivitis (VKC) is a chronic bilateral inflammation of the conjunctiva, commonly associated with a personal or family history of atopy. It is characterized by severe itching, foreign body sensation, thick ropy discharge, photophobia and conjunctival injection. VKC has palpebral, limbal and mixed forms. The classical conjunctival sign in palpebral VKC is the presence of giant papillae, which are predominantly seen on the superior tarsal conjunctiva. The limbal form occurs in dark skinned individuals and the papillae tend to occur at the limbus and have a thick gelatinous appearance. Clinical findings and laboratory investigations support the presence of IgE mediated type 1 hypersensitivity reaction. Involvement of CD4 T helper (Th2) driven type IV hypersensitivity has also been confirmed. There has been an increase in the prevalence of allergic disorders in recent years and exaggerated manifestations of these diseases have been recognized in patients living with Human immunodeficiency virus.